FORMULATION AND CHARACTERISATION OF GASTRORETENTIVE IN SITU GEL LOADED WITH GLYCYRRHIZA GLABRA L. EXTRACT FOR GASTRIC ULCER - R., VIJAYASHREE; PRIYA, SNEH; JYOTHI, DIVYA; JAMES, JAINEY P. (International Journal of Applied Pharmaceutics, 2024)
Objective: The study aimed to formulate and evaluate the gastroretentive in situ gelling system of Glycyrrhiza glabra L. extract to increase the gastric residence time and provide sustained release of the drug, thereby avoiding disadvantages such as frequent dosing, patient non-compliance and low bioavailability. Methods: The in-situ gel was prepared by pH-triggered gelation method by using sodium alginate and gellan gum as polymers, sodium citrate as a crosslinking agent, and calcium carbonate as a floating agent. Formulation and optimization of in situ gels were achieved by 32 factorial design by using Design-Expert Software to determine the influence of independent variables such as concentration of sodium alginate and gellan gum on viscosity, gel strength, the onset of flotation, and drug release at 12 h. Results: The viscosity, gel strength, onset of flotation and drug release at 12h of optimized formulation were found to be 568.89 cps, 42.91 sec, 53.17 sec and 82.69%, respectively. The floating duration of all in-situ gels was found to be more than 12 h. All the formulations showed drug content in the range of 83.55% to 95.28%. The in vitro release profile of the drug extract from all the formulations appeared to follow the Higuchi model, which concludes that the drug release was controlled by diffusion mechanism. The FTIR study indicates no chemical incompatibility between drug extract and other excipients. Conclusion: Hence, a novel gastroretentive in situ gelling system of Glycyrrhiza glabra L. could be prepared for sustained oral delivery to increase patient compliance with reduced dosing frequency and increased residence time of the drug in the stomach.